Assessment of critical loads instigating voltage instability in transmission network using novel load tracing capable index LQP_LT and PSS/E tools validation - Verayiah R.; Mohamed A.; Abidin I.Z.; Shareef H. (Engineering and Scientific Research Groups, 2023)
Reactive power; Software testing; Stability; Voltage control; Contingency state; Deregulated environments; Power system simulations; Power transfers; Transmission systems; Transmission-service pricing; Voltage instability; Voltage stability improvement; Electric power transmission